First Experience Using Navigation-Guided Radiofrequency Kyphoplasty for Sacroplasty in Sacral Insufficiency Fractures - Klingler, J.-H.; Kluge, P.; Sircar, R.; Kogias, E.; Scholz, C.; Krüger, M. T.; Scheiwe, C.; Hubbe, U. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To evaluate the efficacy and safety of navigation-guided radiofrequency kyphoplasty for sacroplasty in patients with sacral insufficiency fractures.Methods: In this single-center retrospective observational study, four consecutive patients with sacral insufficiency fractures were treated with navigation-guided radiofrequency kyphoplasty for sacroplasty between April 2010 and May 2012. Symptom characteristics, pain duration and pain intensity were recorded for each patient. Cement extravasation was evaluated in thin-sliced and triplanar reconstructed CT scans of the sacrum.Results: Four female patients with painful sacral insufficiency fractures and extensive osteopenic areas significantly improved from an average pre-treatment VAS score of 8.3 ± 0.5 to 2.3 ± 1.0 (p < 0.001) on the first postoperative day and to 1.3 ± 1.9 (p < 0.004) at follow-up (mean, 20.1 weeks). Slight cement extravasations were observed without evidence of being symptomatic. No major complications or procedure-related morbidity were noted.Conclusion: From the limited experience in four patients, navigation-guided radiofrequency kyphoplasty appears to be a safe and effective treatment option for sacral insufficiency fractures even though asymptomatic cement extravasation was noted. The use of navigation based on intraoperative 3 D images simplifies the positioning of the navigated bone needles via the long axis approach. The radiofrequency kyphoplasty system provides the possibility to administer a sufficient amount of bone cement with a well-defined viscosity over the entire period of the procedure leading to high security and low cement extravasation. Sacroplasty provides rapid and enduring pain relief and facilitates prompt mobilization.
Keywords: spine; navigation; osteoporosis; sacroplasty; sacral insufficiency fracture; radiofrequency kyphoplasty